2023
DOI: 10.9734/afsj/2023/v22i1610
|View full text |Cite
|
Sign up to set email alerts
|

Popular Products of Sesame (Sesamum indicum L.) Consumed in India and their Quality Concern

Abstract: Sesame is the most consumed oilseed available in different varieties in India. It is eaten as a whole seed, ground, roasted, powdered, oil, or defatted meal in preparation for traditional and popular ready-to-eat sweet and savory food items. It is used in household recipes, bakery items like biscuits, buns, bagel bread, weaning foods etc. Sesame seeds and its products are rich sources of energy, protein, iron, calcium, magnesium, zinc, antioxidants and essential fatty acids. The food products of sesame are ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Finally, the ω-6/ω-3 ratios were the best in S2 (0.93%) followed by S4 (11.49%), in contrast to S1 and S3 which had unfavourable ratios, 117.94% and 36.97%, respectively. As reported in the literature, sesame seed meal may be incurporated into other foods because its oil has a high amount of unsaturated fatty acids such as linoleic acid, acid, palmitoleic acid, and traces of linolenic acid (Nagar et al, 2022). Also, Yuksel, Karaman and Kayacier (2014) observed that flaxseed flour had a high amount of total unsaturated fatty acids (ω-3) that can be used in wheat chips as a functional omega-3 ingredient.…”
Section: Chemical Compositionmentioning
confidence: 90%
See 1 more Smart Citation
“…Finally, the ω-6/ω-3 ratios were the best in S2 (0.93%) followed by S4 (11.49%), in contrast to S1 and S3 which had unfavourable ratios, 117.94% and 36.97%, respectively. As reported in the literature, sesame seed meal may be incurporated into other foods because its oil has a high amount of unsaturated fatty acids such as linoleic acid, acid, palmitoleic acid, and traces of linolenic acid (Nagar et al, 2022). Also, Yuksel, Karaman and Kayacier (2014) observed that flaxseed flour had a high amount of total unsaturated fatty acids (ω-3) that can be used in wheat chips as a functional omega-3 ingredient.…”
Section: Chemical Compositionmentioning
confidence: 90%
“…They can also be combined with other ingredients to make value-added products that can prevent malnutrition and improve nutritional status at a lesser cost. Sesame seeds are incorporated in several foods as snacks and sweets, for example, sprinklers, which are made with whole or coarsely ground flour (Nagar, Agrawal & Agrawal, 2022). Due to their unique bioactive component, including sesamin, sesaminol, and γ-tocopherols, which have antioxidant properties, antihypertensive effects, and the ability to increase plasma tocopherol and stimulate the activity of vitamin E, which helps in the prevention of cancerous and cardiac diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Sesame ( Sesamum indicum L . ), belonging to the Pedaliaceae family, is widely used in Middle Eastern cuisine as cooking oil and seasoning ingredients (Nagar & Agrawal, 2022). Sesame seeds are rich sources of vitamin E, polyunsaturated fatty acids (PUFAs), fiber, phytosterol, and bioactive lignans including sesamin, sesamolin, sesamol, and episesamin (Andargie et al, 2021; Nagar & Agrawal, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Sesame (Sesamum indicum L.), belonging to the Pedaliaceae family, is widely used in Middle Eastern cuisine as cooking oil and seasoning ingredients (Nagar & Agrawal, 2022). Sesame seeds are rich sources of vitamin E, polyunsaturated fatty acids (PUFAs), fiber, phytosterol, and bioactive lignans including sesamin, sesamolin, sesamol, and episesamin (Andargie et al, 2021;Nagar & Agrawal, 2022). Research has shown that sesame seeds can have beneficial effects in lowering blood pressure (Khosravi-Boroujeni et al, 2017), improving lipid profile (Khalesi et al, 2016), reducing inflammatory factors (Rafiee et al, 2021), and increasing the antioxidant capacity (Raeisi-Dehkordi et al, 2020) of the body.…”
mentioning
confidence: 99%